Pengaruh Profitabilitas, Leverage Dan Arus Kas Operasi Terhadap Penghindaran Pajak (Studi Kasus Pada Perusahaan Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023) - Yolanda, Yolanda; Zahran, Wahidin Septa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to analyze profitability, leverage and operating cash on tax avoidance in banking sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. This study uses descriptive quantitative approach methods and Nonprobability Sampling as a sampling technique with a sample of 21 banking sector companies from the Indonesia Stock Exchange (IDX) in 2021-2023. Data is obtained from the company's financial statements and annual reports. In conclusion, profitability has a positive effect on tax avoidance, leverage has a positive effect on tax avoidance, operating cash flow has a positive effect on tax avoidance, together profitability, leverage and operating cash flow have a positive effect on tax avoidance. Data analysis uses multiple linear regression analysis. The results of the determination coefficient test were 39.7%, meaning that the influence of profitability, leverage and operating cash variables on tax avoidance was 39.7%, while 60.3% was influenced by other factors that were not studied in this study.